1996
DOI: 10.1074/jbc.271.17.10194
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Characterization of SmLIM, a Developmentally Regulated LIM Protein Preferentially Expressed in Aortic Smooth Muscle Cells

Abstract: Differentiated, quiescent vascular smooth muscle cells assume a dedifferentiated, proliferative phenotype in response to injury, one of the hallmarks of arteriosclerosis. Members of the LIM family of zinc-finger proteins are important in the differentiation of various cells including striated muscle. We describe here the molecular cloning and characterization of a developmentally regulated smooth muscle LIM protein, SmLIM, that is expressed preferentially in the rat aorta. This 194-amino acid protein has two L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
96
1
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(102 citation statements)
references
References 42 publications
4
96
1
1
Order By: Relevance
“…RNA Preparation, Northern Blot Analysis, and in Situ Hybridization-Total RNA was prepared from mouse organ tissue and cultured cells as described (33). Northern blot analysis was performed as described (33).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…RNA Preparation, Northern Blot Analysis, and in Situ Hybridization-Total RNA was prepared from mouse organ tissue and cultured cells as described (33). Northern blot analysis was performed as described (33).…”
Section: Methodsmentioning
confidence: 99%
“…Northern blot analysis was performed as described (33). In situ hybridization was performed as described (33).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These proteins are CRP1 (29,48), CRP2/SmLIM (38,49), and CRP3/ MLP (39). There is growing evidence that CRPs mediate protein-protein interaction by their two LIM domains (50,51).…”
Section: Figmentioning
confidence: 99%
“…Studies in both chick and rat have revealed that CRP2 (also referred to as SmLIM) is present at highest levels in arterial samples (Jain et al 1996;Louis et al 1997), and subsequent work has focused on a potential role for CRP2 in the vascular system (Jain et al 1998). Here we describe the pattern of csrp2 expression in the developing and adult mouse.…”
mentioning
confidence: 99%